Socio-strategical Knowledge: An Essential Necessity for the Iranian Nursing Society - Shomoossi, Nematullah; Nematshahi, Mohammad; Roshanzadeh, Mostafa; Tajabadi, Ali (Advances in Nursing & Midwifery, 2020)
Dear Editor, The realm of nursing has always confronted complex moral and social issues and has been developed by the effects of newly emerging knowledges [1]. One of these areas is the socio- strategical knowledge that is the central authority of professional nursing and prepares nurses to question the status quo and dominant structures in society which affect the health of individuals and communities [2]. Nurses are the largest human resources in the field of health care. Thay have many duties and responsibilities. Currently, there are no accurate statistics on the number of nurses in Iran, but according to statistics provided by the nursing organization, there are approximately 200,000 nurses working in hospitals. Now Iranian nursing and heart nursing associations, as well as four newly established Iranian nursing administration, adult nursing care, community health and geriatric and children and infants nursing care along with other available potentials such as deputy of nursing care of the ministry of health, nursing board, nursing organization can help to strengthen the socio- strategical aspect of nursing in Iran. Nowadays, the Iranian nursing society is highly in demand of establishing strong foundations in social and strategical contexts. As far as the social dimension is concerned, the society’s view of nursing is not appropriate in terms of structure, abilities, dignity and character. Professional nursing relationships with other disciplines are not satisfactory [3], while nursing is a multidisciplinary area which utilizes humanities such as psychology, sociology, philosophy-logic, theology and basic sciences such as mathematics, physics and chemistry, and a small percentage of this great discipline is the health science. Therefore, the role of nursing is low in the successes that are occasionally given to the physical and mental health of the community [4]. On the other hand, moving towards professional autonomy with strategies such as setting up and strengthening patient education units and keeping them active, the presence of nurses in health centers and the emphasis on professional role is helpful in achieving this goal. AS for the strategical aspect, however, the need for the Iranian nursing society is apparently more perceptible because one of the important ways to access resources is to strongly influence on the national levels of the managerial positions and decision making. Nurses must participate in various strategical and social elections and gradually become involved in decision-making positions in order to protect the nursing profession and the general health of the community. It is imperative that nurses delegate individuals to decision-making seats, where this is a universally agreed upon strategy. A large number of nurses in the nursing associations, nursing and community-based organizations are active in elections, and serve as a source of strength and self-esteem in this profession.